Valorization of passion fruit stalk by the preparation of cellulose nanofibers and immobilization of trypsin - Rodríguez-Restrepo, Yeimy A. (2020)
Fibers from passion fruit stalks were first recovered with a pulping and bleaching process. Two mechanical treatments were further applied to the fibers, homogenization (with and without ultrasound), and blender application. The effect of those treatments on fibers was evaluated. The chemical composition of the different stages of fibers undergoing treatment were measured according to TAPPI standards and were also analyzed by SEM, FTIR, and XRD. Trypsin was immobilized by adsorption and by covalent binding. The biocatalyst support-trypsin was evaluated in terms of immobilization yield, retention, and enzymatic activity. The experimental results demonstrated that the final cellulose concentration in the fibers was 44 % higher than that in the raw stalks. The cellulose nanofibers obtained by homogenization presented a size distribution between 20200 nm, and the application of ultrasound did not show a significant effect on size (between 50 to 300 nm). Trypsin immobilized using glycidol presented an immobilization yield of 67 % and presented higher retention and enzymatic activity (1.17±0.05 U/mg protein and 44.0±2.0 %, respectively). These results show that passion fruit stalks can be successfully used as a source of cellulose nanofibers and also can be used as carriers for the immobilization of trypsin.